Global assessment of spatiotemporal changes of frequency of terrestrial wind speed - Yanan Zhao; Shijing Liang; Yi Liu; Tim R McVicar; Cesar Azorin-Molina; Lihong Zhou; Robert J H Dunn; Sonia Jerez; Yingzuo Qin; Xinrong Yang; Jiayu Xu; Zhenzhong Zeng (Environmental Research Letters)
Wind energy, an important component of clean energy, is highly dictated by the disposable wind speed within the working regime of wind turbines (typically between 3 and 25 m s ^−1 at the hub height). Following a continuous reduction (‘stilling’) of global annual mean surface wind speed (SWS) since the 1960s, recently, researchers have reported a ‘reversal’ since 2011. However, little attention has been paid to the evolution of the effective wind speed for wind turbines. Since wind speed at hub height increases with SWS through power law, we focus on the wind speed frequency variations at various ranges of SWS through hourly in-situ observations and quantify their contributions to the average SWS changes over 1981–2021. We found that during the stilling period (here 1981–2010), the strong SWS (⩾ 5.0 m s ^−1 , the 80th of global SWS) with decreasing frequency contributed 220.37% to the continuous weakening of mean SWS. During the reversal period of SWS (here 2011–2021), slight wind (0 m s ^−1 < SWS < 2.9 m s ^−1 ) contributed 64.07% to a strengthening of SWS. The strengthened strong wind (⩾ 5.0 m s ^−1 ) contributed 73.38% to the trend change of SWS from decrease to increase in 2010. Based on the synthetic capacity factor series calculated by considering commercial wind turbines (General Electric GE 2.5-120 model with rated power 2.5 MW) at the locations of the meteorological stations, the frequency changes resulted in a reduction of wind power energy (−10.02 TWh yr ^−1 , p < 0.001) from 1981 to 2010 and relatively weak recovery (2.67 TWh yr ^−1 , p < 0.05) during 2011–2021.